Proceedings of 1994 IEEE Industry Applications Society Annual Meeting
DOI: 10.1109/ias.1994.377470
|View full text |Cite
|
Sign up to set email alerts
|

Starting and synchronization of permanent magnet hysteresis motors

Abstract: This paper presents the design and application of permanent magnets in the hysteresis motor with a view to improve the overall performances of such motor. The novel rotor consists of 36% Cobalt steel alloys with Neodymium Boron Iron permanent magnets. This hybrid design combines advantageous performance features of both the typical permanent magnet motors and the conventional hysteresis motors. The machine models for steady state and run-up performances are derived. Using state variable equations, starting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The motor torque is thoroughly developed with both a permanent magnet and hysteresis effects at synchronous speed [13]. The dq-axis equations of the motor are derived from the equivalent circuits and are expressed as in [14].…”
Section: Modeling Of the Hysteresis Motormentioning
confidence: 99%
“…The motor torque is thoroughly developed with both a permanent magnet and hysteresis effects at synchronous speed [13]. The dq-axis equations of the motor are derived from the equivalent circuits and are expressed as in [14].…”
Section: Modeling Of the Hysteresis Motormentioning
confidence: 99%
“…Park's equations are obtained by setting the speed of the stator frame equal to the rotor speed, as shown in Fig. 3 [9].…”
Section: Equivalent Circuitmentioning
confidence: 99%
“…However, the disadvantages of these motors are low power factor, high magnetizing current, and low efficiency. Moreover, when a random disturbance happens, the rotor of the hysteresis motor oscillates around the synchronous speed at a low frequency equal to [3][4][5] Hz. This phenomenon is called "hunting".…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results of this research showed that the hysteresis-reluctance motor has better performance characteristics in comparison to the conventional hysteresis motor. In [4], a cylindrical PMHS motor was investigated, and by using state-space equations, the performance characteristics of this motor were predicted in the time domain. This method in comparison to the previous analytical methods has some advantages such as the capability of prediction of the machine performance characteristics even in the case of having asymmetric or nonlinear parameters.…”
Section: Introductionmentioning
confidence: 99%